1971
DOI: 10.1139/g71-089
|View full text |Cite
|
Sign up to set email alerts
|

ALLELIC SEX DETERMINATION IN A LOWER HYMENOPTERAN,NEODIPRION NIGROSCUTUMMIDD

Abstract: In the course of breeding from an original pair of N. nigroscutum, diploid ♀ ♀ (2n = 14), in addition to haploid ♀ ♀ (n = 7), were found by weighing the fourth generation of offspring. Diploid ♀ ♀ occurred only among the progeny of mated ♂ ♂, the progeny of virgins consisting solely of haploid ♀ ♀. Diploid ♀ ♀ are usually 20–30% heavier than their haploid brothers and are produced at the expense of sisters. The haploid ♀ ♀ mated readily but only 1 diploid ♀ out of 150 achieved successful copulation, as shown b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
50
0

Year Published

1975
1975
2009
2009

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(50 citation statements)
references
References 1 publication
0
50
0
Order By: Relevance
“…The common initiation of experimental stocks with very small numbers of wild-caught individuals increases the importance of this bias. For example, the stock of Neodiprion nigroscutum used by Smith & Wallace (1971) had its origin in a single, wildcaught pair.…”
Section: Evidence For Csd In Arrhenotokous Speciesmentioning
confidence: 99%
See 1 more Smart Citation
“…The common initiation of experimental stocks with very small numbers of wild-caught individuals increases the importance of this bias. For example, the stock of Neodiprion nigroscutum used by Smith & Wallace (1971) had its origin in a single, wildcaught pair.…”
Section: Evidence For Csd In Arrhenotokous Speciesmentioning
confidence: 99%
“…Even if all mortality was due to diploid males, the observed sex ratio of diploids is still significantly different from 1:1 CSD with one or a few loci Neodiprion nigroscutum. In the fourth generation of a culture started from a single, wild-caught pair of sawflies, Smith & Wallace (1971) noted a bimodal distribution of male pupal weight. Cytological study revealed the existence of haploid and diploid males, with the latter, on average, 20-30 per cent heavier.…”
Section: Jmcookmentioning
confidence: 99%
“…Only two members of the suborder Symphyta have been studied (Smith & Wallace 1971;Several independent loci The above equations give the probability of any initially dimorphic locus being in state X, Y or Z after t generations. As Crozier's model specified independent loci, the fixation probability of each sex determination locus does not depend on any other sex locus.…”
Section: Tests Of Mutt/locus Csdmentioning
confidence: 99%
“…This system of single locus complementary sex determination (CSD) has also been demonstrated in another parasitoid wasp Diadromus puichellus (Periquet et a!., 1993), as well as the bees Apis mellifera (Mackensen, 1951;Woyke, 1965) and A. cerana (Woyke, 1979;Hoshiba eta!., 1981) and the sawfly Athalia rosae (Naito & Suzuki, 1991). It appears that single locus CSD also operates in the sawfly Neodiprion nigroscutum (Smith & Wallace, 1971), the fire ant Solenopsis invicta (Hung et a!., 1972(Hung et a!., , 1974Hung & Vinson, 1976;Ross & Fletcher, 1985, 1986 and the stingless bee Melipona quadrifasciata (Camargo, 1979), although data from these species do not strictly exclude a multilocus model (Cook, 1993). Diploid males have been detected in more than 20 other 130 species of Hymenoptera, comprising ants, bees and wasps, but comprehensive tests of single locus CSD have not been carried out in these species (Cook, 1993) It is clear that single locus CSD does not apply to all Hymenoptera as prolonged inbreeding does not lead to diploid male production in some species of parasitoid wasps in the superfamily Chalcidoidea (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…sl-CSD has been documented in more than 40 species distributed widely over the major taxonomic subgroups of the order Hymenoptera (Smith and Wallace, 1971;Cook, 1993b;Beukeboom, 1995), and is the prevalent system in the clade that includes the Ichneumonoidea (Whiting, 1943;Butcher et al, 2000b) and the aculeate (stinging) Hymenoptera (Mackensen, 1950;Ross and Fletcher, 1985;Duchateau et al, 1994). The wide distribution of sl-CSD across multiple clades suggests that it may be an ancestral character state in Hymenoptera (Cook, 1993b).…”
Section: Introductionmentioning
confidence: 99%